Isaac N. Phillips, The Revised Ordinances of the City of Bloomington, A.D. 1876: Comprising the general ordinances, acts of incorporation, and other laws affecting the City of Bloomington (Bloomington, IL: Leader Steam Printing and Publishing House, 1876), 47. Licenses, Division 11. Shooting Galleries, §1-3 - (:unkn) unknown (General Publisher, 1876)
Prohibited owning, keeping, or running any shooting gallery or target shooting without obtaining a license. Violators fined twenty-five dollars for each offense. Such licenses will last for one year and cost ten dollars or fifty cents per day.
--
Keywords: SHOOTING RANGES OR GALLERIES